Lymphomas presenting as chest wall tumors - Witte, Biruta (German Medical Science, 2006)
Four cases of thoracic lymphoma mimicking chest wall tumors are presented. As resection is not the treatment of first choice in lymphomas, pretherapeutical evaluation of chest wall tumors should include a thoroughly staging and a biopsy for histopathological diagnosis. Chest wall destruction due to an anterior mediastinal mass, or a chest wall tumor associated with mediastinal lymph node enlargement, could be suspicious of thoracic lymphoma. Lymphoma with chest wall involvement mostly turns out to be Hodgkin's disease or large B-cell lymphoma. Stage and histopathological diagnosis have major impact on treatment and prognosis. Therapy is chemotherapy or chemo-radiation.